Professor Valeriy Ivanovich Kazansky (1894–1978) (on the 130th anniversary of his birth) - Al. А. Kurygin; V. V. Semenov (Вестник хирургии имени И.И. Грекова)
A prominent Russian surgeon, talented scientist and teacher, one of the founders of the development of thoracic surgery in the USSR, Honored Scientist of the RSFSR (1965), Doctor of Medical Sciences, Professor Valery Ivanovich Kazansky was born on October 14, 1894 in the village of Turgenevo, Tula Governorate, into a priest’s family. After graduating from the Tula Gymnasium with a medal, he entered the Imperial Military Medical Academy, which he graduated from in 1919. For two years, he served as a military doctor in the Red Army on the Eastern Front. After demobilization, he worked in the People’s Commissariat of Public Health, from 1925 to 1934, he headed the Surgical Department at the Hospital in Turtkul, and then in Chardzhou (Turkmenistan). In 1935, V. I. Kazansky transferred to work at the 2nd Moscow Medical Institute in the Clinic of Professor S. I. Spasokukotsky and simultaneously headed the Surgical Clinic of the Central Institute of Blood Transfusion (until 1947). In 1938, he defended his doctoral dissertation “Spontaneous non-tuberculous pyopneumothorax and its treatment”. During the Great Patriotic War, V. I. Kazansky was the consultant to the Northwestern and Western Fronts on blood transfusion issues, worked as the Professor-consultant at the Hospital of the Ministry of Railways, which specifically admitted victims with gunshot wounds to the chest. At the same time, from 1943, he served as the chief surgeon of the Moscow Department of Health, and from 1946 to the end of 1952, he held the position of chief oncologist of the USSR Ministry of Health. In 1953, he was elected the head of the Surgery Department of the Central Institute for Advanced Medical Training. For 30 years, V. I. Kazansky studied the problem of treating patients with esophageal cancer and for numerous works, including three monographs, he was awarded the N. N. Burdenko Prize. In 1973, the fundamental monograph “Surgery of Esophageal Cancer” was published. Valery Ivanovich was the author and co-author of about 200 scientific works, including 10 monographs, under his supervision 32 candidate and 8 doctoral dissertations were defended. Professor V. I. Kazansky died on March 30, 1978 and was buried in Moscow at the Nikolo-Arkhangelskoye Cemetery.